2019
DOI: 10.1002/qj.3616
|View full text |Cite
|
Sign up to set email alerts
|

What global reanalysis best represents near‐surface winds?

Abstract: Since global reanalysis datasets first appeared in the 1990s, they have become an essential tool to understand the climate of the past. The wind power industry uses those products extensively for wind resource assessment, while several climate services for energy rely on them as well. Nowadays various datasets coexist, which complicates the selection of the most suitable source for each purpose. In an effort to identify the products that best represent the wind speed features at turbine hub heights, five state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
198
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 271 publications
(214 citation statements)
references
References 52 publications
11
198
0
5
Order By: Relevance
“…We used the ERA5 reanalysis product (Copernicus Climate Change Service 2017) to represent observed historical meteorological conditions (Olauson 2018, Urraca et al 2018, Ramon et al 2019. The full ERA5 record available at time of analysis was used, 1979-2018, providing 40 years of data.…”
Section: Meteorological Datamentioning
confidence: 99%
“…We used the ERA5 reanalysis product (Copernicus Climate Change Service 2017) to represent observed historical meteorological conditions (Olauson 2018, Urraca et al 2018, Ramon et al 2019. The full ERA5 record available at time of analysis was used, 1979-2018, providing 40 years of data.…”
Section: Meteorological Datamentioning
confidence: 99%
“…Furthermore, Oueslati et al (2017) have reported that the ERA-Interim reanalysis is able to capture very well the annual cycle and its interannual variability of the US heat-index (an index that is used in the present study over the Sahel). There is additional evidence that ERA5 is the reanalysis that offers the best representation of various near surface meteorological products including near surface moisture and wind speed (e.g., Olauson 2018;Ramon et al 2019), which are used in this paper (see Table 1). ERA5 is therefore well suited to this research.…”
Section: Data and Derivation Of Thermal Indicesmentioning
confidence: 99%
“…Our analysis used meteorological reanalysis from the European Centre for Medium-Range Weather Forecasts Interim Reanalysis (ERA-Interim; [38]) at the native resolution of 0.75 • in latitude and longitude. ERA-Interim provides a good representation of near-surface winds in the Southern Hemisphere in comparison with other leading reanalyses [39]. For the forward and backward trajectory runs shown in Figure 3a,b, respectively, there is reasonable consistency that the enhanced backscatter features observed with the Buckland Park lidar between 11 and 13 km height on 30 April link back to the Calbuco eruption on 22 April.…”
Section: Buckland Park Scattering Ratiomentioning
confidence: 64%